Differential positive TSPOT assay responses to ESAT-6 and CFP-10 in health care workers. (December 2016) - Agarwal, Saroochi; Nguyen, Duc T.; Lew, Justin D.; Teeter, Larry D.; Yamal, Jose-Miguel; Restrepo, Blanca I.; Brown, Eric L.; Dorman, Susan E.; Graviss, Edward A.
Abstract: Background: The TSPOT. TB (TSPOT) diagnostic test for latent tuberculosis infection is based on a cell-mediated response to the Mycobacteria tuberculosis antigens, ESAT-6 and/or CFP-10, producing an "interferon-gamma footprint". We investigated the within-sample and within-subject variability of positive TSPOT assays due to the individual assay antigens' reactivity. Methods: Positive TSPOT assay frequencies due to ESAT-6 or CFP-10 among health care workers (HCWs) at 6-month intervals for 18 months were compared. Differences in result interpretation (positive or negative) for ESAT-6 and CFP10 and potential prognostic factors were investigated. Results: There were 576 positive results in 8805 TSPOT assays representing 2418 participants. A significant difference was detected in positive TSPOT results due to a positive response to either ESAT-6, CFP-10 or both antigens at baseline through 12 M ( p  < 0.001), but not for the 18 M follow-up. Gender, ethnicity, occupation, previous positive tuberculin skin test (TST) and study site were significantly associated with specific antigen positivity. Conclusions: Among our HCW samples with positive TSPOT assays, CFP-10 induced a larger proportion of positive TSPOT results than ESAT-6. Potential causes for this finding include: BCG vaccinated subpopulations, certain jobs, history of positive TST, U.S. birth, and study site. A high proportion of single-positive specimens may reflect false-positives results.